Application of three-dimensional aromatic material, perovskite solar cell and preparation method thereof

By doping three-dimensional aromatic materials into the perovskite active layer of perovskite solar cells, the problems of insufficient long-term stability and hysteresis effects of perovskite solar cells are solved, and the effect of improving photoelectric conversion efficiency and stability is achieved.

CN119768016AActive Publication Date: 2025-04-04NANCHANG INST OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510238682.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-04
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

The long-term stability of perovskite solar cells and the presence of hysteresis effects affect their commercial application.

Method used

Three-dimensional aromatic materials such as trianyl tricarboxylate (TATA), tetra(4-carboxyphenyl)methane (TCPM) and trinitrotrianyl (TNHA) are used as dopants for the perovskite active layer to regulate the nucleation and growth kinetics of perovskite grains and improve the crystallization quality and stability of the film.

Benefits of technology

It effectively improves the photoelectric conversion efficiency of perovskite solar cells, reduces the hysteresis effect, and enhances the environmental stability and service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768016A_ABST
    Figure CN119768016A_ABST
Patent Text Reader

Abstract

The invention provides application of a three-dimensional aromatic material, a perovskite solar cell and a preparation method of the perovskite solar cell, and belongs to the technical field of solar cell materials. The three-dimensional aromatic material is triphenylamine triformate, tetra (4-carboxyphenyl) methane or trinitro triphenylamine, and is used as a dopant of the perovskite active layer. The preparation method of the perovskite solar cell comprises the following steps: depositing a NiOx thin film on the surface of a conductive substrate to prepare a hole transport layer; under the protection of nitrogen, a perovskite precursor solution doped with a three-dimensional aromatic material is spin-coated on the hole transport layer through a spin-coating method to form a perovskite thin film, and a perovskite active layer is prepared; continuously depositing a phenylethylamine iodized salt film to prepare a modification layer; depositing a PCBM thin film to prepare an electron transport layer; and evaporating a metal electrode to obtain the perovskite solar cell. The three-dimensional aromatic material is used as the doping agent of the perovskite active layer, so that the hysteresis performance and the environmental stability of the perovskite solar cell are improved, and the photoelectric conversion efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cell materials, and in particular relates to the application of three-dimensional aromatic materials, perovskite solar cells and preparation methods thereof. Background Art

[0002] Perovskite materials are a general term for a class of materials with a calcium titanate crystal structure, usually abbreviated as ABX3. Due to their excellent optoelectronic properties, ideal optical band gap and good thermal stability, they are widely used in the light absorption layer of solar cells, also known as the perovskite active layer; all-solid-state solar cells prepared based on perovskite materials are called perovskite solar cells, or PSCs for short. PSCs combine the advantages of direct band gap, high absorption coefficient, low exciton binding energy, high carrier mobility, long carrier lifetime and diffusion distance, high defect tolerance, etc., and have simple preparation process, low cost and high photoelectric conversion efficiency. However, the commercial application of PSCs still faces certain challenges, mainly reflected in the lack of long-term stability and hysteresis effect.

[0003] One of the key functional layers that affects the stability of PSCs is the perovskite active layer. The perovskite active layer is mainly a perovskite polycrystalline film grown by the solution method. It is rich in defects on the surface and grain boundaries, which easily leads to non-radiative recombination of carriers, affecting the efficiency and stability of the device. In addition, the perovskite active layer is sensitive to environmental factors such as humidity and temperature, which will cause irreversible decomposition of the material layer, thereby reducing the stability between layers and destroying the contact between layers, which has a negative impact on the overall stability of the device, and ultimately causes the life of PSCs to show a significant attenuation.

[0004] The hysteresis effect refers to the fact that when measuring the current-voltage (JV) characteristics of perovskite solar cells, the curves obtained by the forward scan and the reverse scan do not overlap, and there is a hysteresis phenomenon. The main reasons are: the perovskite lattice is mismatched with the nickel oxide lattice of the hole transport layer; the rapid growth process leads to residual strain in the perovskite film; and the presence of voids between grains, which leads to ion migration and causes the hysteresis effect. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide the application of three-dimensional aromatic materials, perovskite solar cells and preparation methods thereof, aiming to solve at least one technical problem in the background technology.

[0006] The present invention is achieved in that: The first aspect of the present invention provides an application of a three-dimensional aromatic material, wherein the three-dimensional aromatic material has a spatial rotationally symmetrical structure and comprises at least three carboxylic acid phenyl groups or three nitrophenyl groups; the three-dimensional aromatic material is triphenylamine triformate, trinitrotriphenylamine or tetrakis(4-carboxyphenyl)methane; The three-dimensional aromatic material is used as a dopant for the perovskite active layer; The structural formula of the triphenylamine triformate is as follows: ; The structural formula of the tetrakis(4-carboxyphenyl)methane is as follows: ; The structural formula of the trinitrotriphenylamine is as follows: .

[0007] The second aspect of the present invention provides a perovskite solar cell, which comprises a conductive substrate, a hole transport layer, a perovskite active layer, a modification layer, an electron transport layer and a metal electrode stacked in sequence from bottom to top; the perovskite active layer is doped with the above three-dimensional aromatic material; The three-dimensional aromatic material is doped in a perovskite precursor solution at a doping amount of 1 mg / mL to 4 mg / mL, and is deposited on a hole transport layer to form a perovskite film, thereby obtaining the perovskite active layer.

[0008] Preferably, the conductive substrate is made of conductive glass; The hole transport layer is made of NiO x , The material of the modification layer is phenylethylamine iodide dissolved in isopropanol; The material of the electron transport layer is 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 dissolved in chlorobenzene; The metal electrode is made of gold, silver or copper.

[0009] Preferably, the thickness of the hole transport layer is 10 nm to 30 nm; the thickness of the perovskite active layer is 500 nm to 700 nm; and the thickness of the metal electrode is 150 nm to 200 nm.

[0010] The third aspect of the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: providing a conductive substrate; Deposition of NiO on the surface of conductive substrate x Thin film, preparing hole transport layer; The three-dimensional aromatic material is doped in a perovskite precursor solution at a doping amount of 1 mg / mL to 4 mg / mL. Under nitrogen protection, the perovskite precursor solution is spin-coated on the hole transport layer by a spin coating method, and then heated and cooled in sequence to form a perovskite film to obtain the perovskite active layer. Depositing a phenylethylamine iodide salt film on the surface of the perovskite active layer to obtain the modified layer; Depositing a 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 (PCBM) thin film on the surface of the modified layer to obtain the electron transport layer; A metal electrode is evaporated on the electron transport layer to prepare a perovskite solar cell.

[0011] Preferably, when preparing the perovskite active layer, the total spin coating time is 30s to 45s, 150mL to 250mL of chlorobenzene is added dropwise at 10s to 15s, and after spin coating, the conductive substrate is placed on a hot stage and heated at 100°C to 150°C for 30min to 60min.

[0012] Preferably, the preparation step of the hole transport layer comprises: NiO x The nanoparticles were dissolved in deionized water at a concentration of 5 mg / mL to 30 mg / mL and vibrated to form NiO x Solution; NiO was spin-coated x The solution is spin-coated on a conductive substrate at a spin-coating rate of 2000 rpm to 5000 rpm for 30 s to 40 s, and then heat-treated at 120° C. to 150° C. for 10 min to 30 min to obtain a hole transport layer.

[0013] Preferably, the preparation step of the modification layer comprises: dissolving phenethylamine iodide in isopropanol solution to prepare 1 mg / mL~5 mg / mL phenethylamine iodide solution; spin coating the phenethylamine iodide solution on the surface of the perovskite active layer by spin coating to obtain the modification layer, the spin coating rate is 3000rpm~6000rpm, and the spin coating time is 30s~50s.

[0014] Preferably, the preparation step of the electron transport layer includes: dissolving 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 in chlorobenzene in a concentration range of 18 mg / mL~25 mg / mL, heating and stirring at 40°C~60°C to obtain a PCBM solution; spin coating the PCBM solution on the surface of the modified layer at a speed of 2000rpm~2500rpm, and then treating at 80°C~90°C for 20min~40min to obtain the electron transport layer.

[0015] Preferably, the metal electrode is formed by vacuum thermal evaporation method, and the evaporation rate is 0.5Å / s~5.0Å / s.

[0016] Compared with the prior art, the present invention uses triphenylamine triformate (TATA), tetrakis(4-carboxyphenyl)methane (TCPM), and trinitrotriphenylamine (TNHA) as perovskite active layer dopants to improve the hysteresis performance and environmental stability of perovskite solar cells and improve the photoelectric conversion efficiency.

[0017] The present invention provides a dopant having a spatial rotationally symmetrical structure and comprising polycarboxylic acid phenyl or polynitrophenyl, which can regulate the nucleation and growth kinetics of perovskite grains and improve the film-forming quality of perovskite thin films. The prepared perovskite active layer has high crystal quality, a grain size of micrometer order, and good light absorption performance.

[0018] At the same time, TATA, TCPM, and TNHA located at the grain boundaries of the perovskite active layer can bond the grains in multiple dimensions, passivate interface defects, and inhibit the migration of ions at the interface. Therefore, the performance of perovskite solar cells is effectively improved, the photoelectric conversion efficiency is increased, and there is no obvious hysteresis effect.

[0019] In addition, the application of TATA, TCPM, and TNHA materials can also improve the ability of perovskite solar cells to block water vapor in the air, thereby improving the stability and service life of the battery. After placing the unpackaged perovskite solar cells in high-humidity air for 240 hours, they still maintain a photoelectric conversion efficiency of more than 83%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell of the present invention; Figure 2 The hydrogen nuclear magnetic resonance spectra of the dopant and the FAPbI3 perovskite containing the dopant in Example 1, Example 8 and Example 12; Figure 3 The SEM images of the FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 4 X-ray diffraction patterns of FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 5 The transient fluorescence spectra of the FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 6 Partial Fourier infrared spectra of FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 7 The current density-voltage curves of the forward scan and reverse scan of the FAPbI3 perovskite solar cells prepared in Example 1, Example 8, and Example 12 are shown.

[0021] Illustration: 1-conductive substrate; 2-hole transport layer; 3-perovskite active layer; 4-modification layer, 5-electron transport layer, 6-metal electrode. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] like Figure 1 As shown, a perovskite solar cell includes a conductive substrate 1, a hole transport layer 2, a perovskite active layer 3, a modification layer 4, an electron transport layer 5 and a metal electrode 6 which are stacked in sequence from bottom to top.

[0024] The perovskite active layer 3 is doped with a three-dimensional aromatic material, wherein the three-dimensional aromatic material is triphenylamine triformate or tetrakis(4-carboxyphenyl)methane or trinitrotriphenylamine; Among them, the structural formula of triphenylamine triformate (TATA) is as follows: ; The structural formula of tetrakis(4-carboxyphenyl)methane (TCPM) is as follows: ; The structural formula of trinitrotriphenylamine (TNHA) is as follows: .

[0025] A method for preparing a perovskite solar cell comprises steps S1 to S6.

[0026] S1. providing a conductive substrate; Indium tin oxide ITO conductive glass or tin fluoride FTO conductive glass is used as the conductive substrate. The laser-etched conductive substrate is ultrasonically cleaned with deionized water, acetone, and ethanol for fifteen minutes respectively, then blown dry with nitrogen, and finally treated with ozone plasma for ten minutes.

[0027] S2. Depositing NiO on the surface of the conductive substrate x Thin film, preparing hole transport layer; First, sodium hydroxide was added dropwise to a 0.2M Ni(NO3)2·6H2O aqueous solution to make the pH value of the solution 10, and a precipitate was obtained after stirring for about 30 minutes; The precipitate was filtered and washed twice, and then transferred to a drying oven at about 80°C and dried for about 8 hours; The dried powder was placed in a muffle furnace and calcined at about 270°C for 2 hours to obtain black NiO. x Nanoparticles; NiO x The nanoparticles were dissolved in deionized water at a concentration of 5 mg / mL to 30 mg / mL and vibrated to form NiO x Solution; Then, NiO was spin-coated x The solution is spin-coated on a conductive substrate at a spin-coating rate of 2000 rpm to 5000 rpm for 30 s to 40 s; Finally, the hole transport layer is heat treated at 120°C to 150°C for 10min to 30min, and the thickness of the formed hole transport layer is 10nm to 30nm.

[0028] S3, depositing a perovskite film on the surface of the hole transport layer to obtain a perovskite active layer; Triphenylamine triformate or tetrakis (4-carboxyphenyl) methane or trinitrotriphenylamine is doped in the perovskite precursor solution, and the doping amount is 1 mg / mL~4 mg / mL, and the concentration of the doping amount is based on the solvent in the perovskite precursor solution; in a specific implementation, the material of the perovskite is any perovskite material allowed in the art, and the following embodiment is illustrated by YPbX3 material, wherein Y is at least one of Cs, NH2CH=NH2 (FA), CH3NH3 (MA), and X is at least one of Br and I; Under nitrogen protection, the perovskite precursor solution is spin-coated on the hole transport layer by a spin coating method, the total spin coating time is 30s to 45s, 150mL to 250mL of chlorobenzene is added dropwise at 10s to 15s, and the conductive substrate is placed on a hot stage after spin coating, heated at 100°C to 150°C for 30min to 60min, and a perovskite film is formed after cooling to obtain the perovskite active layer; In a specific implementation, the perovskite precursor solution is prepared by a conventional solvent method, and the specific reaction parameters and steps can be adjusted according to actual needs and are not specifically limited here.

[0029] S4, depositing a phenylethylamine iodide salt film on the surface of the perovskite active layer to obtain the modified layer; Phenylethylamine iodide can passivate the surface defects of perovskite film, hinder the ion leakage of perovskite layer, improve the quality of perovskite film and the stability of perovskite solar cells; Specifically, 1 mg / mL to 5 mg / mL phenethylamine iodide solution is prepared by dissolving phenethylamine iodide in isopropanol solution, and the phenethylamine iodide solution is spin-coated on the surface of the perovskite active layer by spin coating, the spin coating rate is 3000 rpm to 6000 rpm, and the spin coating time is 30 s to 50 s.

[0030] S5, depositing a PCBM film on the surface of the modified layer to obtain an electron transport layer; Specifically, 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 (PCBM) is dissolved in chlorobenzene in a concentration range of 18 mg / mL to 25 mg / mL, and heated and stirred at 40°C to 60°C for about 12 hours to obtain a PCBM solution; the PCBM solution is spin-coated on the surface of the modified layer at a rotation speed of 2000rpm to 2500rpm, and then treated at 80°C to 90°C for 20min to 40min to obtain the electron transport layer.

[0031] S6, evaporating a metal electrode on the electron transport layer to produce a perovskite solar cell; The metal electrode is any one of gold, silver or copper, and is formed by vacuum thermal evaporation method with an evaporation rate of 0.5Å / s~5.0Å / s.

[0032] The present invention dopes a functional symmetrical small molecule organic substance with a three-dimensional structure into the perovskite active layer, thereby improving the quality of the perovskite film, thereby enhancing the stability of the perovskite solar cell device and suppressing the hysteresis effect.

[0033] Compared with the currently common symmetrical small molecules such as biphenyl dicarboxylic acid (BCLA), phthalic acid (PPA), etc., the present invention uses triphenylamine tricarboxylate material (TATA), tetrakis (4-carboxyphenyl) methane material (TCPM), and trinitrotriphenylamine (TNHA) with spatial rotational symmetric structure and multiple carboxylic acid / nitric acid groups as dopants to achieve perovskite crystal growth regulation and defect passivation in a large range in the three-dimensional direction, inhibit ion migration and improve its stability. The present invention fully utilizes the unique nano-scale size and controllable 3D molecular configuration of the dopant. Using the nano-scaffold formed by its self-assembly as a template, the nucleation and crystal growth behavior of perovskite can be precisely regulated at the nanoscale, the micromorphology can be improved, and the crystallinity and stability can be enhanced; in addition, TATA and TCPM have multiple carboxylic acid groups, and TNHA has multiple nitric acid groups, which can effectively passivate perovskite crystal defects in the 3D direction, inhibit ion migration, form electrically active tight connections between grains, and effectively release the tensile strain of perovskite grains in all directions. While ensuring sufficient photoelectric conversion efficiency of perovskite solar cells, the hysteresis performance and environmental stability of perovskite solar cell devices are improved.

[0034] Example 1 This embodiment 1 is a method for preparing a TATA-doped FAPbI3 perovskite solar cell, and the steps include: S1. Using indium tin oxide (ITO) conductive glass as a conductive substrate, the laser-etched conductive substrate was ultrasonically cleaned with deionized water, acetone, and ethanol for fifteen minutes respectively, then dried with nitrogen, and finally treated with ozone plasma for ten minutes; S2. Sodium hydroxide was added dropwise to a 0.2M Ni(NO3)2·6H2O aqueous solution to make the pH value of the solution 10, and a precipitate was obtained after stirring for 30 minutes; then, the precipitate was filtered and washed twice, and then transferred to a drying oven and dried at 80°C for 8 hours; the dried powder was placed in a muffle furnace and calcined at 270°C for 2 hours to obtain black NiO x Nanoparticles; NiO x The nanoparticles were dissolved in deionized water at a concentration of 20 mg / mL and shaken to form NiO x The solution was then spin-coated on a conductive substrate at a rate of 4000 rpm for 30 s, followed by a heat treatment at 140°C for 130 min. The resulting hole transport layer had a thickness of about 20 nm. S3, preparing a TATA-doped FAPbI3 perovskite precursor solution, and then depositing a FAPbI3 perovskite active layer on the surface of the hole transport layer; specifically: (1) Dissolve 1.6 mol of PbI2 and 1.6 mol of FAI in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the volume ratio of DMF to DMSO is 4:1, stir at room temperature for about 20 h, and then add 2 mg of TATA to obtain a perovskite precursor solution; (2) Under nitrogen protection and at a temperature of 15°C to 25°C, the perovskite precursor solution was spin-coated on the hole transport layer at a speed of 4000 rpm. The total spin-coating time was 30 seconds. 200 mL of chlorobenzene was added after 10 seconds. After spin coating, the substrate was placed on a hot stage and heated at 150°C for 30 minutes. After cooling, a FAPbI3 perovskite film was formed to obtain a perovskite active layer with a thickness of about 600 nm. S4, phenylethylamine iodide was dissolved in isopropanol at a concentration of 2 mg / mL, and spin-coated on the surface of the perovskite active layer at 4000 rpm for 40 s to obtain a modified layer; S5. Dissolve 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 (PCBM) in chlorobenzene to obtain a PCBM solution with a concentration of 23 mg / mL, and heat and stir at 60°C for 12 hours; spin-coat the PCBM solution on the phenylethylamine iodide modified layer at a speed of 2000 rpm, and then treat at 90°C for 30 minutes to obtain an electron transport layer; S6. A silver electrode was evaporated on the electron transport layer at a rate of 2.0Å / s. The film thickness of the silver electrode was about 150nm, and a TATA-doped FAPbI3 perovskite solar cell was prepared.

[0035] Example 2 This embodiment 2 is a method for preparing a TATA-doped methylamine cesium lead iodide perovskite solar cell. The difference between this embodiment and the embodiment 1 is that the perovskite material in the perovskite precursor solution in the perovskite active layer has a molecular formula of FA 0.78 MA 0.18 Cs 0.04 The preparation steps of PbI3, perovskite precursor solution specifically include: 1.6 mol of PbI2, 1.6 mol of CH(NH2)2I (FAI), 0.075 mol of CsI, 0.15 mol of CH3NH3I (MAI) and 0.1875 mol of CH3NH3Cl (MACl) were dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of DMF to DMSO was 4:1, stirred at room temperature for about 20 h, and then 2 mg of TATA was added and stirred evenly to obtain a TATA-doped perovskite precursor solution. During the preparation process, the chlorine element in MACl will turn into chlorine gas and overflow.

[0036] The other steps and parameters are the same as those in Example 1.

[0037] Example 3 This embodiment 3 is a method for preparing a TATA-doped methylamine cesium lead iodine bromine perovskite solar cell. The difference between this embodiment 3 and embodiment 1 is that the perovskite material in the perovskite precursor solution in the perovskite active layer has a molecular formula of FA 0.78 MA 0.18 Cs 0.04 PbI 2.88 Br 0.12 , the steps for preparing the perovskite precursor solution specifically include: 1.6 mol of PbI2, 1.6 mol of CH(NH2)2I (FAI), 0.075 mol of CsI, 0.15 mol of CH3NH3Br (MABr) and 0.1875 mol of CH3NH3Cl (MACl) were dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the volume ratio of DMF to DMSO was 4:1. Stir at room temperature for about 20 h, then add 2 mg of TATA and stir evenly to obtain a TATA-doped perovskite precursor solution.

[0038] The other steps and parameters are the same as those in Example 1.

[0039] Example 4 This embodiment 4 is a method for preparing a MAPbI3 perovskite solar cell based on TATA doping. The difference between this embodiment 4 and embodiment 1 is that the perovskite material in the perovskite active layer has a molecular formula of MAPbI3. The steps for preparing the perovskite precursor solution specifically include: 1.6 mol of PbI2 and 1.6 mol of CH3NH3I (MAI) were dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the volume ratio of DMF to DMSO was 4:1. The mixture was stirred at room temperature for about 20 h, and then 2 mg of TATA was added and stirred evenly to obtain a TATA-doped perovskite precursor solution.

[0040] The other steps and parameters are the same as those in Example 1.

[0041] Example 5 This Example 5 is a method for preparing a TATA-doped FAPbI3 perovskite solar cell. The only difference between this method and Example 1 is that the amount of TATA dopant is adjusted to 1 mg, and the other steps and parameters are the same as those in Example 1.

[0042] Example 6 This Example 6 is a method for preparing a TATA-doped FAPbI3 perovskite solar cell. The only difference between this method and Example 1 is that the amount of TATA dopant is adjusted to 3 mg, and the other steps and parameters are the same as those in Example 1.

[0043] Example 7 This Example 7 is a method for preparing a TATA-doped FAPbI3 perovskite solar cell. The only difference between this method and Example 1 is that the amount of TATA dopant is adjusted to 4 mg, and the other steps and parameters are the same as those in Example 1.

[0044] Example 8 This Example 8 is a method for preparing a TCPM-doped FAPbI3 perovskite solar cell. The only difference between it and Example 1 is that the TATA dopant is replaced by the TCPM dopant, and the other steps and parameters are the same as those in Example 1.

[0045] Example 9 This Example 9 is a method for preparing a TCPM-doped caesium lead iodide perovskite solar cell. The only difference between it and Example 2 is that the TATA dopant is replaced by the TCPM dopant, and the other steps and parameters are the same as those in Example 2.

[0046] Example 10 This Example 10 is a method for preparing a TCPM-doped caesium lead iodine bromide perovskite solar cell. The only difference between it and Example 3 is that the TATA dopant is replaced by the TCPM dopant, and the other steps and parameters are the same as those in Example 3.

[0047] Embodiment 11 This Example 11 is a method for preparing a TCPM-doped MAPbI3 perovskite solar cell. The only difference between it and Example 4 is that the TATA dopant is replaced by the TCPM dopant, and the other steps and parameters are the same as those of Example 4.

[0048] Example 12 This Example 12 is a method for preparing a TNHA-doped FAPbI3 perovskite solar cell. The only difference between it and Example 1 is that the TATA dopant is replaced by the TNHA dopant, and the other steps and parameters are the same as those in Example 1.

[0049] Embodiment 13 This Example 13 is a method for preparing a TNHA-doped caesium lead iodide perovskite solar cell. The only difference between it and Example 2 is that the TATA dopant is replaced by the TNHA dopant, and the other steps and parameters are the same as those in Example 2.

[0050] Embodiment 14 This Example 14 is a method for preparing a TNHA-doped caesium lead iodine perovskite solar cell. The only difference between it and Example 3 is that the TATA dopant is replaced by the TNHA dopant, and the other steps and parameters are the same as those in Example 3.

[0051] Embodiment 15 This Example 15 is a method for preparing a TNHA-doped MAPbI3 perovskite solar cell. The only difference between it and Example 4 is that the TATA dopant is replaced by the TNHA dopant, and the other steps and parameters are the same as those of Example 4.

[0052] Comparative Example 1 This comparative example 1 is a method for preparing a dopant-free FAPbI3 perovskite solar cell, which differs from Example 1 only in that the perovskite precursor solution in the perovskite active layer is dopant-free, and the other steps and parameters are the same as those in Example 1.

[0053] Comparative Example 2 This comparative example 2 is a method for preparing a FAPbI3 perovskite solar cell without a modification layer. The only difference between it and Example 1 is that S4 is deleted and there is no modification layer made of phenylethylamine iodide salt; the electron transport layer is prepared directly on the perovskite active layer, and the other steps and parameters are the same as those in Example 1.

[0054] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that TATA is used as the dopant of the organic interface layer instead of the perovskite active layer. The other steps and parameters are the same as those of Example 1.

[0055] The specific S3 of this comparative example 3 is as follows: (1) Dissolve 2 mg of TATA in 1 mL of ethanol solution, apply it on the hole transport layer, and then anneal it at 120 °C for 20 min to obtain a TATA organic interface layer; (2) Dissolve 1.6 mol of PbI2 and 1.6 mol of FAI in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of DMF to DMSO is 4:1, and stir at room temperature for about 20 h to obtain a perovskite precursor solution; under nitrogen protection, at a temperature of 15°C~25°C, spin-coat the perovskite precursor solution on the TATA organic interface layer at a speed of 4000 rpm, and the total spin-coating time is 30 s. Add 200 mL of chlorobenzene after 10 s. After spin coating, place the substrate on a hot stage and heat at 150°C for 30 min. After cooling, a FAPbI3 perovskite film is formed to obtain a perovskite active layer with a thickness of about 600 nm.

[0056] Figure 2 The nuclear magnetic resonance hydrogen spectra of the dopant and the FAPbI3 perovskite containing the dopant in Example 1, Example 8 and Example 12 are shown in FIG. Figure 2 wherein TATA-PVK, TCPM-PVK, and TNHA-PVK are FAPbI3 perovskite films containing corresponding dopants prepared in Example 1, Example 8, and Example 12, respectively; Figure 2 It can be seen that compared with TATA, TCPM, and TNHA, the H element in the nuclear magnetic resonance hydrogen spectra of TATA-PVK, TCPM-PVK, and TNHA-PVK undergoes chemical shift, indicating that TATA, TCPM, and TNHA all interact with PbI2.

[0057] Figure 3 The SEM images of the FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 3 In the example, PVK is the FAPbI3 perovskite film without dopant prepared in Comparative Example 1, TATA-PVK, TCPM-PVK, and TNHA-PVK are the FAPbI3 perovskite films containing corresponding dopants prepared in Example 1, Example 8, and Example 12, respectively. Figure 3 It can be seen that the perovskite films doped with TATA, TCPM, and TNHA have larger grains, and the grains are dense and free of voids.

[0058] Figure 4 The X-ray diffraction patterns of the FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 4 It can be seen that the crystals doped with TATA, TCPM or TNHA have better crystal orientation and crystallinity.

[0059] Figure 5 The transient fluorescence spectra of the FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12; Figure 5 It can be seen that the perovskite films doped with TATA, TCPM, and TNHA have longer carrier lifetimes.

[0060] Figure 6 Partial Fourier infrared spectra of FAPbI3 perovskite films prepared in Comparative Example 1, Example 1, Example 8, and Example 12, Figure 6 It can be seen that in Example 1, Example 8, and Example 12, the C=N vibration peak vibrates from 1709 to 1711, 1711.1, and 1710.6, respectively, indicating that the doped TATA, TCPM, TNHA, and FA all interact with each other.

[0061] Figure 7 The current density-voltage curves of the forward scan and reverse scan of the FAPbI3 perovskite solar cells prepared in Example 1, Example 8 and Example 12 are shown; Figure 7 It can be seen that the forward scanning and reverse scanning curves of perovskite solar cells prepared based on TATA, TCPM, and TNHA basically coincide, that is, they have a lower hysteresis effect.

[0062] The specific test method for the performance of perovskite solar cells is as follows: standard simulated sunlight (AM1.5G, 100mW / cm 2 ) to test the current density-voltage (JV) characteristic curve of the perovskite solar cell device; the performance parameters such as open circuit voltage, short circuit current density, fill factor, photoelectric conversion efficiency, etc. are obtained from the JV characteristic curve; The overlap of the JV characteristic curves of the forward scanning (FS) from low voltage to high voltage and the reverse scanning (RS) from high voltage to low voltage characterizes the hysteresis effect of the device and is an important evaluation index of the device performance. The hysteresis coefficient is used for quantification. The hysteresis coefficient HI (%) of the present invention = 100% × (PCE RS -PCE FS ) / PCE RS ; PCE RS 、PCE FSThey are the photoelectric conversion efficiency of reverse scanning and forward scanning respectively; the smaller the hysteresis coefficient is, the smaller the hysteresis effect of the device is.

[0063] The performance test results of the perovskite solar cells prepared in Examples 1 to 15 and Comparative Examples 1 to 3 were compared, as shown in Table 1.

[0064] Table 1

[0065] In Table 1, V OC is the open circuit voltage, in V; J SC is the short-circuit current density, in mA / cm 2 ; FF is the fill factor; PCE is the photoelectric conversion efficiency.

[0066] As can be seen from Table 1, the present invention uses triphenylamine triformate (TATA), tetrakis(4-carboxyphenyl)methane (TCPM), and trinitrotriphenylamine (TNHA) as perovskite active layer dopants, respectively, to improve the hysteresis performance and environmental stability of the perovskite solar cell device, and to improve the photoelectric conversion efficiency.

[0067] In addition, it can be seen from Examples 1 to 4, Examples 8 to 11, and Examples 12 to 15 that the dopant of the present invention has a wide range of applications and is suitable for various types of perovskite materials.

[0068] From the comparison of Example 1 and Example 5 to Example 7, it can be seen that as the amount of dopant increases, the photoelectric conversion efficiency of the prepared perovskite solar cell first increases and then decreases, and the hysteresis coefficient increases. The reason is that excessive dopant affects the carrier transport and extraction of the film; therefore, the amount of dopant is set to 1 mg / ml~4 mg / ml, preferably 1 mg / ml~3 mg / ml, and the optimal amount is 2 mg / ml.

[0069] By comparing Example 1, Example 8, Example 12 with Comparative Example 1, it can be seen that compared with no dopant, the performance of the perovskite solar cell prepared after doping with TATA, TCPM, and TNHA is better than that of the undoped perovskite solar cell.

[0070] From the comparison between Example 1 and Comparative Example 2, it can be seen that the performance of the perovskite solar cell without the modification layer is lower than that of the cell with the modification layer. The reason is that the modification layer helps to improve the stability and carrier extraction of the perovskite solar cell.

[0071] By comparing Example 1 with Comparative Example 3, it can be seen that the photoelectric conversion efficiency of the solar cell prepared by using triphenylamine triformate (TATA) as the organic interface layer is also very excellent, but still lower than that of Example 1, and its hysteresis performance is not effectively improved, and the hysteresis coefficient is much higher than that of Example 1.

[0072] The unpackaged perovskite solar cells prepared in Comparative Examples 1 to 3 and Examples 1 to 15 were placed in air (with a humidity of not less than 70%), and the changes in the photoelectric conversion efficiency PCE with the increase of the placement time were tested, and the retention rate was calculated. PCE retention rate = (PCE0-PCE n ) / PCE0; PCE0, PCE n They are the photoelectric conversion efficiency of the perovskite solar cell device after being placed in the air for n hours initially and before being packaged. The results are shown in Table 2. The greater the PCE retention rate, the higher the device's ability to block water vapor and the stronger its stability.

[0073] Table 2

[0074] As can be seen from Table 2, as the placement time increases, the photoelectric conversion efficiency decreases due to the erosion of the perovskite solar cell device by moisture in the external environment. After being placed for 240 hours, the perovskite solar cell prepared by the present invention can still maintain a PCE of more than 83%, and can still maintain a PCE of about 70% or more after being placed for 480 hours, which shows that the addition of dopant materials for the perovskite active layer of the present invention can effectively improve the barrier ability of the perovskite solar cell device to water vapor in the air. Compared with Example 1, the barrier ability of the perovskite solar cell prepared by Comparative Example 1 without a dopant and Comparative Example 2 without a modified layer to water vapor in the air is greatly reduced. By comparing Example 1 with Comparative Example 3, it can be seen that the solar cell prepared by using triphenylamine triformate (TATA) as an organic interface layer has a weaker barrier ability to water vapor in the air than the solar cell prepared by using TATA as a dopant.

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Application of three-dimensional aromatic materials, characterized in that, The three-dimensional aromatic material is triphenylamine triformate, tetrakis(4-carboxyphenyl)methane or trinitrotriphenylamine; the three-dimensional aromatic material is used as a dopant for the perovskite active layer; The structural formula of the triphenylamine triformate is as follows: ; The structural formula of the tetrakis(4-carboxyphenyl)methane is as follows: ; The structural formula of the trinitrotriphenylamine is as follows: 。 2. A perovskite solar cell, characterized in that The perovskite solar cell comprises a conductive substrate, a hole transport layer, a perovskite active layer, a modification layer, an electron transport layer and a metal electrode stacked in sequence from bottom to top; The perovskite active layer is doped with the three-dimensional aromatic material according to claim 1; The three-dimensional aromatic material is doped in a perovskite precursor solution at a doping amount of 1 mg / mL to 4 mg / mL, and is deposited on a hole transport layer to form a perovskite film to obtain the perovskite active layer.

3. The perovskite solar cell according to claim 2, characterized in that: The conductive substrate is made of conductive glass; The hole transport layer is made of NiO x , The material of the modification layer is phenylethylamine iodide dissolved in isopropanol; The material of the electron transport layer is 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 dissolved in chlorobenzene; The metal electrode is made of gold, silver or copper.

4. The perovskite solar cell according to claim 2, characterized in that: The thickness of the hole transport layer is 10nm~30nm; the thickness of the perovskite active layer is 500nm~700nm; and the thickness of the metal electrode is 150nm~200nm.

5. A method for preparing a perovskite solar cell, characterized in that: Used to prepare the perovskite solar cell according to any one of claims 2 to 4; the preparation method comprises the following steps: providing a conductive substrate; Deposition of NiO on the surface of conductive substrate x Thin film, preparing hole transport layer; The three-dimensional aromatic material is doped in a perovskite precursor solution at a doping amount of 1 mg / mL to 4 mg / mL. Under nitrogen protection, the perovskite precursor solution is spin-coated on the hole transport layer by a spin coating method, and then heated and cooled in sequence to form a perovskite film to obtain the perovskite active layer. Depositing a phenylethylamine iodide salt film on the surface of the perovskite active layer to obtain the modified layer; Depositing a 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 thin film on the surface of the modified layer to obtain the electron transport layer; A metal electrode is evaporated on the electron transport layer to prepare a perovskite solar cell.

6. The method for preparing a perovskite solar cell according to claim 5, characterized in that: When preparing the perovskite active layer, the total spin coating time is 30s to 45s, 150mL to 250mL of chlorobenzene is added dropwise at 10s to 15s, and after spin coating, the conductive substrate is placed on a hot stage and heated at 100°C to 150°C for 30min to 60min.

7. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The preparation steps of the hole transport layer include: NiO x The nanoparticles were dissolved in deionized water at a concentration of 5 mg / mL to 30 mg / mL and vibrated to form NiO x Solution; NiO was spin-coated x The solution is spin-coated on a conductive substrate at a spin-coating rate of 2000 rpm to 5000 rpm for 30 s to 40 s, and then heat-treated at 120° C. to 150° C. for 10 min to 30 min to obtain a hole transport layer.

8. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The preparation step of the modification layer includes: dissolving phenethylamine iodide salt in isopropanol solution to prepare 1 mg / mL~5 mg / mL phenethylamine iodide salt solution, and spin coating the phenethylamine iodide salt solution on the surface of the perovskite active layer by spin coating to obtain the modification layer, the spin coating rate is 3000rpm~6000rpm, and the spin coating time is 30s~50s.

9. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The preparation steps of the electron transport layer include: dissolving 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]-C-61 in chlorobenzene with a concentration range of 18 mg / mL to 25 mg / mL, heating and stirring at 40°C to 60°C to obtain a PCBM solution; spin coating the PCBM solution on the surface of the modified layer at a speed of 2000rpm to 2500rpm, and then treating at 80°C to 90°C for 20min to 40min to obtain the electron transport layer.

10. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The metal electrode is formed into a film by a vacuum thermal evaporation method, and the evaporation rate is 0.5Å / s~5.0Å / s.

Citation Information

Patent Citations

  • Reverse planar perovskite solar cell device with guanidine hexafluorophosphate interface modification layer and preparation method of reverse planar perovskite solar cell device

    CN111933801A

  • Porphyrin-modified organic-inorganic hybrid perovskite nano-film material and preparation method thereof

    CN113921722A

  • Method for improving efficiency and stability of perovskite solar cell and perovskite solar cell

    CN115440889A

  • Perovskite solar cell and preparation method thereof

    CN116437672A

  • Perovskite solar cell buried interface modifier and preparation method and application thereof

    CN119110602A